Experimental Study on Electrical Resistivity of Cement-Stabilized Lead-Contaminated Soils. (27th August 2018) - Cao, Zhiguo; Xiang, Lian; Peng, Erxing; Li, Kai
Abstract : Geotechnical applications based on soil resistivity measurement are becoming more popular in recent years. In order to explore the potential application of the electrical resistivity method in stabilization/solidification of contaminated soils, two kinds of lead-contaminated soils stabilized with cement were prepared, and the electrical resistivity and unconfined compressive strength of specimens after curing for various periods were measured. The test results show that a high lead content leads to a low value of electrical resistivity of cement-stabilized soils, and increasing cement content and curing time result in a significant increase in electrical resistivity. The reduction in porosity and degree of saturation, as a result of the cement hydration process, leads to an increase in electrical resistivity. The ratio of porosity-lead content/cement content-curing time, combining together the effect of lead content, cement content, curing time, and porosity on electrical resistivity of stabilized soils, can be used as a fundamental parameter to assess electrical resistivity of cement-stabilized lead-contaminated soils. Archie's law can be extended to apply to cement-stabilized lead-contaminated soils by using this ratio, replacing the porosity. The new resistivity formula obtained in this paper is just empirical. There is a power function correlation between unconfined compressive strength and electrical resistivity of lead-contaminated soils stabilized with cement. Electrical resistivity measurement can be used as an economical and time-effective method to assess the quality of cement-stabilized lead-contaminated soils in practice.